Influenza Pandemic Outbreaks: Conducting Focus Groups with Rural Communities in Baram, Sarawak - Wah, C.R.J; Mohd-Nor, Rohaya (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Our research aims to explore rural communities' understanding, awareness and attitude towards H1N1 Influenza pandemic outbreaks and prevention measures. We attempt to ascertain their views with regard to the effective use of various media platforms in educating them about the pandemic influenza outbreaks. In 2012, a series of focus group sessions was conducted in Baram, Sarawak. We assess our choice of methodology and approaches in setting-up and conducting these focus groups. Based on our experience, we found that cultural factor, language barrier and level of education (among others) are some issues that a researcher has to consider prior to conduct a focus group to obtain good quality data from the rural participants.